The stand of social responsibility within the strategy of business organization - Drūteikienė, Greta; Seiliutė, Jovita (Publishing House of the Wrocław University of Economics, 2009)
Implementation of social responsibility is crucial in respect to the environment of the organization and moral condition of the society. Social responsibility anticipates from a business organization the voluntary responsiveness and responsi-bility in solving certain social issues abundant and still robustly mounting in modern society. The link between business organization (strategic) management and social responsibility ought to be discussed. In addition, we should search for opportunities to incorporate the element of social responsibility in the business organization management and its strategy. The aim of this article is to discuss the possibilities of integration of social responsibility elements into the business organization’s strategy. The scientific literature analysis is applied to attain the aim of the article. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 109-118